R&D Intensity: Peran Board Size, Board Independence, dan Board Participation - Zulkarnain Zulkarnain; Trisa Inna Fitriyani (UNHI Press, 2023)
Indonesia's innovation rate is still low and industry participation in innovation is less than 20%. In a company, the board of directors play an important role in innovation with the greatest power to select R&D projects and to evaluate their effectiveness. Nevertheless, the uncertainty of expected R&D results is a consideration for directors to implement innovation in the company. Then this study aims to examine R&D intensity, and how board size, board independence, and board participation affect it. The manufacturing industry listed on the Indonesia Stock Exchange during the 2017-2019 period were the subject of the study. The sample selection used purposive sampling with the sample used in this study were 48 companies and 144 observation data. The results of this study indicated that board size, board independence, and board participation had no effect on R&D intensity. This showed that the board of directors were not the only party that made decisions related to R&D, its role as an agent made the decisions taken and the policies determined in line with the interests of shareholders.